Hubungan antara Pola Asuh Orang Tua dengan Perilaku Bullying di SMP an-Namiroh Pekanbaru - Siregar, Alini Salsada; Harahap, Elly Warnisah; Ekowati, Endang (ANWARUL, 2023)
Bullying or harassment is an act committed by a person or group of people using intense and repetitive words or actions towards another person or group of people, causing pressure or depression. Violence in education is behavior that goes beyond the boundaries of the moral code and the educational code, both in physical form and in the form of human rights harassment. Bullying of others, especially behavior that occurs in educational settings, is a concern for many groups. In this study, researchers wanted to learn more about bullying, its impact, and the factors behind bullying at SMP An Namiroh Pekanbaru. And also know the parenting style of parents in building the character of their children. This study used a qualitative method to understand the types of harassment occurring at SMP An Namiroh Pekanabaru. The purpose of this study was done because bullying is common from year to year, so parenting style influences a child's personality. The result of this study is that families whose parents can be thought of as having a role in preventing bullying behavior in adolescents by SMP An Namiroh Pekanbaru, was carried out by applying parenting models. teaching children, communicating with children, being close to children and by communicating. closely with the school so that they can manage children in a kind and non-threatening manner.